1982
DOI: 10.1063/1.443370
|View full text |Cite
|
Sign up to set email alerts
|

The effect of randomly distributed surface bumps on local field enhancements in surface enhanced Raman spectroscopy

Abstract: A model is presented for determining the enhancement of local electromagnetic fields which occurs close to rough metal surfaces through surface plasmon excitation. The model considers a random distribution of metal hemispheroids on a perfectly conducting flat plane. The electrodynamics of this system is described using the long wavelength approximation and with only the dipole coupling between different hemispheroids included. The square of the local field is averaged over all locations on the surface to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…This model considers a random distribution of metal hemispheroids on a perfectly conducting flat plane. He concluded that surface roughness contributes 10 2 to 10 3 to the overall enhancement with a frequency dependence which is close to that seen experimentally (Laor et al 1982).…”
Section: Sers Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…This model considers a random distribution of metal hemispheroids on a perfectly conducting flat plane. He concluded that surface roughness contributes 10 2 to 10 3 to the overall enhancement with a frequency dependence which is close to that seen experimentally (Laor et al 1982).…”
Section: Sers Studiessupporting
confidence: 57%
“…At the same time, the SERS response is site dependent. Schatz performed calculations and confirm that the local fields are larger on curved regions than flat surfaces (Laor et al 1982). Chemical contributions that can affect SERS response depend of the distinctive surface structure and/or redistribution of conduction electrons which will be manifested as an altered dielectric constant in the surface region are possible explanation to unusual enhancement effects.…”
Section: Sers Studiesmentioning
confidence: 99%
“…The approach is useful, since rough metal surfaces, as well as its relationship with SERS enhancement, have been extensively explored. 30,32,34 Consequently, the details associated with the enhancement generated by rough metal surfaces can provide insight into the possible mechanism for the enhancement effect of various aggregate geometries on SERS.…”
Section: -7mentioning
confidence: 99%
“…Although calculations predict intense fields for the static case, in at least one reference the dimensions for the surface protrusions are predicted to be significantly larger than the actual features observed for rough metal surfaces. 32,33 On the other hand, for the nonstatic case, the dimensions of the calculated protrusions are more accurately represented and are not restricted to extreme prolate parameters for effective SERS enhancement in the visible wavelength range. [32][33][34] Electromagnetic enhancement can be substantial not only for rough metal surfaces but also for a collection of interacting metal colloidal nanoparticles.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation